Five-year survival and durability results of brentuximab vedotin in patients with relapsed or refractory Hodgkin lymphoma - Chen, Robert; Gopal, Ajay K; Smith, Scott E; Ansell, Stephen M; Rosenblatt, Joseph D; Savage, Kerry J; Connors, Joseph M; Engert, Andreas; Larsen, Emily K; Huebner, Dirk; Fong, Abraham; Younes, Anas (Blood, 2016)
Presented here are the 5-year end-of-study results from the pivotal phase 2 trial of brentuximab vedotin in patients with relapsed/refractory (R/R) Hodgkin lymphoma (HL) after failed hematopoietic autologous stem cell transplantation. At 5 years, the overall patient population (N = 102) had an estimated overall survival (OS) rate of 41% (95% confidence interval [CI]: 31-51) and progression-free survival (PFS) rate of 22% (95% CI: 13-31). Patients who achieved a complete response (CR) to brentuximab vedotin (N = 34) had estimated OS and PFS rates of 64% (95% CI: 48-80%) and 52% (95% CI: 34-69%), respectively. The median OS and PFS were not reached in CR patients, with 13 patients (38% of all CR patients) remaining in follow-up and in remission at study closure. Of the 13 patients, 4 received consolidative hematopoietic allogeneic stem cell transplant, and 9 (9% of all enrolled patients) remain in sustained CR without receiving any further anticancer therapy after treatment with brentuximab vedotin. Of the patients who experienced treatment-emergent peripheral neuropathy, 88% experienced either resolution (73%) or improvement (14%) in symptoms. These 5-year follow-up data demonstrate that a subset of patients with R/R HL who obtained CR with single-agent brentuximab vedotin achieved long-term disease control and may potentially be cured. The trial was registered at www.clinicaltrials.gov as #NCT00848926.